An indirect wireless electromagnetic measurement of flow velocity by an SRR‐based sensing method. Issue 3 (4th December 2021) - Wei, Lusong; Lin, Pujing; Wu, Zhouyi; Wu, Yuting; Huangfu, Jiangtao
Abstract: This study describes an indirect wireless electromagnetic measurement of flow velocity by measuring the state of the SRR in the waveguide. When the fluid exhibits poor sensitivity to electromagnetic wave, the inclination angle between the SRR and the side wall of the waveguide becomes a direct reflection of flow velocity and affects the resonance frequency of the SRR. To be specific, different inclination angles will cause a variable stopband in the passband of the waveguide. By measuring the inclination angle‐sensitive frequency response of the SRR in the waveguide, the flow velocity can be measured indirectly. Based on this principle, an experiment using WR‐187 rectangular waveguide is produced. A new C‐type SRR is designed and placed in the waveguide with variable inclination angles. As revealed from the simulation and experimental results, when the inclination angle varies from 0° to 90°, the resonance frequency of the SRR shifts from 4.145 to 4.226 GHz. On that basis, the flow velocity at one or more places can be obtained.